Pray bold [large type] : dare to ask and believe big - Osteen, Joel (Faith Words, 2025)
This book explores the idea of approaching prayer with boldness and faith, encouraging readers to move beyond routine or limited requests and instead ask for transformative outcomes in their lives. Emphasizing a connection between mindset, prayer, and spiritual results, the author presents guidance on shifting thought patterns, articulating specific desires, and cultivating belief in divine intervention. The text focuses on themes of personal growth, faith, and spiritual empowerment within a Christian context.